Nurturing children's development through healthy eating and active living: Time for policies to support effective interventions in the context of responsive emotional support and early learning. (19th November 2022) - Skouteris, Helen; Green, Rachael; Chung, Alexandra; Bergmeier, Heidi; Amir, Lisa H.; Baidwan, Sukhpreet Kaur; Chater, Angel Marie; Chamberlain, Catherine; Emond, Ruth; Gibbons, Kay; Gooey, Michelle; Hatzikiriakidis, Kostas; et al.
Abstract: Fostering the growth, development, health, and wellbeing of children is a global priority. The early childhood period presents a critical window to influence lifelong trajectories, however urgent multisectoral action is needed to ensure that families are adequately supported to nurture their children's growth and development. With a shared vision to give every child the best start in life, thus helping them reach their full developmental potential, we have formed the International Healthy Eating Active Living Matters (HEALing Matters) Alliance. Together, we form a global network of academics and practitioners working across child health and development, and who are dedicated to improving health equity for children and their families. Our goal is to ensure that all families are free from structural inequality and oppression and are empowered to nurture their children's growth and development through healthy eating and physical activity within the context of responsive emotional support, safety and security, and opportunities for early learning. To date, there have been disparate approaches to promoting these objectives across the health, community service, and education sectors. The crucial importance of our collective work is to bring these priorities for early childhood together through multisectoral interventions, and in so doing tackle head on siloed approaches. In this Policy paper, we draw upon extensive research and call for collective action to promote equity and foster positive developmental trajectories for all children. We call for the delivery of evidence‐based programs, policies, and services that are co‐designed to meet the needs of all children and families and address structural and systemic inequalities. Moving beyond the "what" is needed to foster the best start to life for all children, we provide recommendations of "how" we can do this. Such collective impact will facilitate intergenerational progression that builds human capital in future generations.